Management of abdominal trauma patients in a peripheral hospital of Eastern India – A prospective study - Pankaj Kumar Sarkar; Debashis Biswas; Somnath Biswas; Samanta, Riddhisundar (Asian Journal of Medical Sciences, 2025)
Background: Abdominal trauma is a common surgical problem in patients attending emergency departments of all peripheral medical colleges like ours. As it consumes a lot of health resources, this becomes quite a significant public health burden. We conducted an epidemiological study regarding age, sex, etiology, clinical presentation, and management on these patients of our medical college. We also re-evaluate the routine use of contrast-enhanced computed tomography (CECT) scan in management of abdominal trauma. Aims and Objectives: This study aims to identify the various causes of abdominal trauma in peripheral regions and to classify the different clinical presentations of abdominal trauma and evaluate the effectiveness of conservative management. Materials and Methods: We had conducted this prospective study in a tertiary care center from February 2022 to August 2024. We had conducted thorough clinical examination and whole abdomen radiology (Straight X-ray abdomen and sonology) of all the patients after proper resuscitation in the emergency ward. As emergency CECT scan of abdomen is not available round the clock in our peripheral medical college, we have to use four quadrant puncture and diagnostic peritoneal lavage in few patients with abnormal clinical and or radiological (Ultrasonography and X-ray) findings. Few patients underwent emergency laparotomy. The rest were put in conservative management with continuous monitoring, among them few patients underwent delayed laparotomy. Results: During the study, 168 patients were admitted. Of these, 24 underwent emergency laparotomy after resuscitation, while 144 were managed conservatively. Among the conservatively managed patients, 21 later required delayed laparotomy based on clinical and radiological findings. A total of 29 patients underwent CECT scans. The primary cause of injury was road traffic accidents (RTA), with physical assault- and cattle-related injuries also notable, especially among the elderly (Chi-square=166.5551, P<0.00001). Conclusion: Non-operative management was successful in most cases in 123 patients, with only 29 requiring a CECT scan. RTAs and physical assaults were the primary causes, with middle-aged individuals being the most affected. In peripheral areas, elderly patients frequently sustain injuries from cow attacks. Most abdominal injuries can be treated conservatively, and well-planned management can significantly reduce mortality.